2000
DOI: 10.1677/joe.0.1640031
|View full text |Cite
|
Sign up to set email alerts
|

Oestradiol is a potent mitogen and modulator of GnRH signalling in alphaT3-1 cells: are these effects causally related?

Abstract: GnRH acts via phospholipase C (PLC) activating G-protein coupled receptors to stimulate secretion of gonadotrophins from gonadotrophs. These cells are also regulated by gonadal steroids, which act centrally to influence GnRH secretion, and peripherally to modulate GnRH action. We have shown that oestradiol can stimulate proliferation and modulate GnRH-stimulated [ H]thymidine incorporation was not stimulated by oestradiol but was reduced to <2% of control by the oestrogen antagonist, raloxifene. The inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Incorporation of [ 3 H]thymidine into newly synthesized DNA was used as a index of cell proliferation (23,37). Cells were seeded in 96-well plates in 250 l DMEM with 10% FCS at a density of 10,000 cells/ml.…”
Section: [ 3 H]thymidine Incorporationmentioning
confidence: 99%
“…Incorporation of [ 3 H]thymidine into newly synthesized DNA was used as a index of cell proliferation (23,37). Cells were seeded in 96-well plates in 250 l DMEM with 10% FCS at a density of 10,000 cells/ml.…”
Section: [ 3 H]thymidine Incorporationmentioning
confidence: 99%
“…3 H]thymidine into newly synthesized DNA was used as a measure of cell proliferation (Williams et al 2000, Everest et al 2001. Cells were seeded into 96-well plates at 2500 cells/well and 24 h later the media were replaced with medium containing 1% FCS and the required amount of Ad GnRH-R. Twenty-four hours later the cells were stimulated with the indicated peptides and 3 days later 10 µl [ 3 H]thymidine were added to each well.…”
Section: Incorporation Of [mentioning
confidence: 99%
“…In both mice and rats, ER␤ is the predominant subtype in ovarian granulosa cells (Couse et al, 1997;Fitzpatrick et al, 1999;O'Brien et al, 1999). In addition, ER␤ seems to be the only ER expressed in the majority of GnRH neurones of female rats (Hrabovszky et al, 2000 a,b;Herbison et al, 2001). In contrast, ER␣ expression is high in both the uterus and the anterior pituitary of the rat (Kuiper et al, 1997;Pelletier et al, 2000;Schreihofer et al, 2000;Wang et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that raloxifene diminished the stimulatory effect of GnRH on LH release in incubated anterior pituitaries (Simard and Labrie, 1987;González et al, 2000). Mechanistically, oestradiol increases the efficiency of GnRH receptors to stimulate phospholipase C and this effect is blocked by raloxifene in ␣T3-1 cells (Williams et al, 2000). In addition, it has been shown that oestradiol increases the number of GnRH receptors in cultured bovine pituitary cells and that this effect is blocked by treatment with tamoxifen (Gregg et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation